2019
DOI: 10.1177/0192623319833906
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability and Safety Study of LifeMesh™, a Novel Self-adhesive Mesh, in Sprague-Dawley Rats

Abstract: Self-adhesive meshes are being developed to avoid complications due to traumatic fixation methods. LifeMesh™ is a novel selfadhesive mesh with a biodegradable gelatin adhesive layer developed for hernia repair. The aim of this study was to assess the safety and biodegradability of LifeMesh in Sprague-Dawley (SD) rats for 6 weeks, in comparison to a bare polypropylene (BPP) mesh fixed with sutures. LifeMesh was tolerated well and its implantation did not result in any adverse local reaction, and its adhesive la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…23 In accordance with the increasing number of medical devices being developed, information on preclinical animal trials with such devices is also growing. [24][25][26][27][28] Specifically for fractional RF devices, it is important to evaluate the consistency and lack of fractional RF effects in the tissue adjacent to the application site, and the lack of any inflammatory reaction at the surrounding tissue. Furthermore, it is essential to observe that normal wound healing process takes place in the application site, with formation of normal skin at this site.…”
Section: Discussionmentioning
confidence: 99%
“…23 In accordance with the increasing number of medical devices being developed, information on preclinical animal trials with such devices is also growing. [24][25][26][27][28] Specifically for fractional RF devices, it is important to evaluate the consistency and lack of fractional RF effects in the tissue adjacent to the application site, and the lack of any inflammatory reaction at the surrounding tissue. Furthermore, it is essential to observe that normal wound healing process takes place in the application site, with formation of normal skin at this site.…”
Section: Discussionmentioning
confidence: 99%
“…141 A new innovative line of research is the manufacture of self-adhesive meshes based on a biodegradable gelatin layer (LifeMesh™) and PP with largepores and lightweight for hernia repair. 142 In a comparative study between the composite LifeMesh™ and PP meshes, LifeMesh™ showed good tolerance and its implantation did not lead to any adverse local reaction. Its adhesive layer degraded during the 4 weeks after implantation and a histopathological examination revealed that the presence of the adhesive contributed to a uniform thickness of the granulation tissue surrounding the mesh, suggesting that the mesh will better integrate with the abdominal wall.…”
Section: Partially Bioabsorbable Meshesmentioning
confidence: 98%
“…The use of this type of mesh resulted in less adherence to the internal organs, which is very important in preventing adverse effects. 142…”
Section: Partially Bioabsorbable Meshesmentioning
confidence: 99%
“…The recovery after inguinal hernia interventions with Parietex™ Progrip TM showed that this type of mesh is able to significantly reduce the surgery time [136]. A new innovative line of research is the manufacture of self-adhesive meshes based on a biodegradable gelatin layer (LifeMesh™) and PP with largepores and lightweight for hernia repair [137]. In a comparative study between the composite LifeMesh™ and PP meshes, LifeMesh™ showed good tolerance and its implantation did not lead to any adverse local reaction.…”
Section: Partially Bioabsorbable Meshesmentioning
confidence: 99%
“…Its adhesive layer degraded during the 4 weeks after implantation and a histopathological examination revealed that the presence of the adhesive contributed to a uniform thickness of the granulation tissue surrounding the mesh, suggesting that the mesh will better integrate with the abdominal wall. The use of this type of mesh resulted in less adherence to the internal organs, which is very important in preventing adverse effects [137].…”
Section: Partially Bioabsorbable Meshesmentioning
confidence: 99%